Evaluation of changes in behavior, heart rate and rectal body temperature in calves during two hours after birth - Terézia Hegerová; Peter Juhás; Jaroslav Dóbi; Klára Vavrišínová (Journal of Central European Agriculture, 2022)
The present experiment focuses on the evaluation of the behavior of Holstein calves in the first two hours after birth. The research took place at the Slovak University of Agriculture Farm in Oponice. The calf sample consisted of 11 individuals. The lying, standing, moving were scored and number of attempts to lift head, latency to head lifting, number of attempts to stand up and latency to stand up, and the number of ears shaking. Behavior was evaluated by next traits: total duration of lying, standing and moving, average duration of one bout lying, standing and moving, percentage rate of lying, standing and moving, number of occurrence of bouts for all scored traits, mean duration inter-event interval for all scored traits. The basic physiological parameters (heart rate – HR and rectal temperature – RT) were measured in four 15 minute intervals during first hour after the birth (M15, M30, M45 and M60). Difference in behavior between first and second hour of observation was tested by non-parametric Kruskal Wallis test. Relation among measured and scored traits was analysed by Spearman rank correlation. The average duration of birth of the examined calf sample was 1 hour and 4 minutes (±0.33 seconds). Positive correlations (P<0.05) between the first and second hour were found in many signs measured after birth (total time of lying, standing and moving, attempts to stand up, latency of standing and ears shaking).